2021
DOI: 10.1186/s12879-021-06226-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus (HBV) viral load, liver and renal function in adults treated with tenofovir disoproxil fumarate (TDF) vs. untreated: a retrospective longitudinal UK cohort study

Abstract: Background Current clinical guidelines recommend treating chronic hepatitis B virus (HBV) infection in a minority of cases, but there are relatively scarce data on evolution or progression of liver inflammation and fibrosis in cases of chronic HBV (CHB) that do not meet treatment criteria. We aimed to assess the impact of TDF on liver disease, and the risk of renal impairment in treated CHB patients in comparison to untreated patients. Methods We s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Patients receiving ADV and TDF therapy even experience more rapid loss in eGFR ( Udompap et al, 2018 ). In contrast, several studies suggested that TDF is not associated with greater degree of kidney injury compared with other NAs ( Trinh et al, 2019 ; Fischer et al, 2021 ) and untreated HBV-infected individuals ( Wang et al, 2021 ). LdT has been demonstrated to improve renal function in CHB patients ( Gane et al, 2014 ), in liver transplant recipients for HBV-related cirrhosis ( Cholongitas et al, 2015 ), and in liver transplant recipients with long-term chronic kidney disease ( Lee et al, 2017 ).…”
Section: Introductionmentioning
confidence: 92%
“…Patients receiving ADV and TDF therapy even experience more rapid loss in eGFR ( Udompap et al, 2018 ). In contrast, several studies suggested that TDF is not associated with greater degree of kidney injury compared with other NAs ( Trinh et al, 2019 ; Fischer et al, 2021 ) and untreated HBV-infected individuals ( Wang et al, 2021 ). LdT has been demonstrated to improve renal function in CHB patients ( Gane et al, 2014 ), in liver transplant recipients for HBV-related cirrhosis ( Cholongitas et al, 2015 ), and in liver transplant recipients with long-term chronic kidney disease ( Lee et al, 2017 ).…”
Section: Introductionmentioning
confidence: 92%
“… 22 Using this dataset, we have reported a bimodal viral load distribution 23 and found evidence of a virological set point in untreated patients. 23 , 24 In a comparison of tenofovir disoproxil fumarate (TDF)-treated vs untreated patients, we reported variable ethnicity distributions across the two groups and some evidence for liver fibrosis progression in the untreated group, highlighting a need for further evidence for expanded treatment. 24 A study of HBsAg and HBeAg clearance dynamics demonstrated that these markers may contribute to prognostication and patient-stratified care and provide a foundation for advancing insights into mechanisms of disease control.…”
Section: What Has It Found?mentioning
confidence: 99%
“… 23 , 24 In a comparison of tenofovir disoproxil fumarate (TDF)-treated vs untreated patients, we reported variable ethnicity distributions across the two groups and some evidence for liver fibrosis progression in the untreated group, highlighting a need for further evidence for expanded treatment. 24 A study of HBsAg and HBeAg clearance dynamics demonstrated that these markers may contribute to prognostication and patient-stratified care and provide a foundation for advancing insights into mechanisms of disease control. 25 The list of publications is available in [ https://hic.nihr.ac.uk ] with ongoing/planned studies presented in Table 2 .…”
Section: What Has It Found?mentioning
confidence: 99%
“…Viewing HBV primarily as an infectious agent builds on established approaches for other chronic blood-borne viruses, such as HCV and HIV, as well as containment approaches to other viruses that threaten population health. Suppressing or clearing HBV or HCV lowers the long-term risks of cirrhosis and liver cancer, liver enzymes and fibrosis scores can improve over time [9], and there is a benefit to quality of life [10]. Approaches to BBV prevention are unified by common principles, as reductions in viraemia translate into a lowered transmission risk.…”
Section: Hbv As An Infectionmentioning
confidence: 99%